Investigating the Implementation of Student-Centered Learning in an EFL Class at an Indonesian Private School - Viona Fatimatul Qoiriah; Aziza Restu Febrianto (CV. Kalimasada Group Profesional, 2025)
Effective education requires teaching methods that can accommodate the needs and potential of each student in class. In this context, student-centered learning (SCL) emerges as an approach that places students at the center of the learning process, where they actively participate in knowledge formation through various activities such as discussions, collaborations, and problem-solving. This approach aims to enhance student engagement, foster independence, and develop critical thinking and communication skills. This research aimed to assess the extent to which the implementation of student-centered learning in the classroom can increase active participation and student involvement in learning. The result of the study shows that students exhibit student-centered learning behaviors while participating in classroom activities. Students are able to engage in discussions with their peers and actively participate in every question posed by the teacher. The benefit of this study is to understand how effective student-centered learning is in English language teaching in class.